The epidemiology and outcomes of perineal and genital burn injury in low- and middle- income countries: a global burn registry study - Panayi, Adriana C.; Didzun, Oliver; Nnabuko, Richard; Sjöberg, Folke; Knoedler, Samuel; Haug, Valentin; Palackic, Alen; Tapking, Christian; Ewerbeck, Nicolas Konstantin; Bigdeli, Amir Khosrow; Kneser, Ulrich; Hundeshagen, Gabriel (Journal of plastic, reconstructive & aesthetic surgery, 2024)
INTRODUCTION: The epidemiology, care, and outcomes of perineal and genital burns (PG) in high-income countries have been previously described, but an analysis of this topic in LMICs has yet to be performed. We use the World Health Organization's Global Burn Registry to fill this gap. - METHODS: The GBR was searched from inception to November 2023 to identify all burn patients, excluding cases from high-income countries. Demographics and mechanism of injury were retrieved. Primary outcomes were length of hospital stay (LOHS), surgical intervention, discharge with physical impairment, and mortality. A multivariate regression analysis was performed controlling for burnt total body surface area (TBSA), age, sex, inhalation injury, mechanism of burn and care center characteristics. - RESULTS: Of 9041 patients identified, 1213 (13.4 %) had PG burns with 136 (1.6 %) isolated to the PG region. PG patients had higher TBSA (p < 0.001) and more inhalation injury (p < 0.001). They had better access to rehabilitation and lower access to theater space for burns (p < 0.001). Multivariable analysis showed that PG patients had longer LOHS (p = 0.001), greater mortality (p < 0.001), were less likely to undergo surgery (p = 0.01) or be discharged home with physical impairment (p = 0.03). - CONCLUSION: Similarities and differences exist between high- and low/middle-income countries in terms of the patterns of injury, care, and recovery in patients with PG burns. The longer LOHS and higher mortality among PG patients, previously reported in high-income countries, are verified. This highlights the importance of greater vigilance when caring for such patients.
Gesehen am 29.01.2025